KARAKTERISTIK PETANI HUTAN DAN RESOLUSI KONFLIK TENURIAL DI HUTAN LINDUNG RIMBO DONOK, KABUPATEN KEPAHIANG, PROVINSI BENGKULU - Senoaji, Gunggung; Hidayat, Muhammad Fajrin; Iskandar, Iskandar (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2020)
Rimbo Donok Protected Forest covers 377,99 hectare area, located in Kepahiang District, Bengkulu Province, Indonesia. The main function of protected forest is to protect life buffer system. Therefore, the land use must be forest. In Rimbo Donok Protected Forest, there has been a change of land use from forest land to crop land. There has been tenurial conflicts in the utilization of forest area. The objective of this study was to determine the characteristics of forest farmer in Rimbo Donok protected forest area and choose to resolve tenurial conflicts. The data of uses were collected through mapping techniques, field observation, and interview. The accidental sampling technique with Slovin Formula was used to select 44 respondents. The results showed that land use of Rimbo Donok Protected Forest in 2016 is entirely crop land. All of this protected forest have been illegaly occupied by people. These people are planting coffe and other agricultural plants in the area. The average land area of head family is 1.33 ha. This conflict resolution of forest utilization should be able to accommodate the socioeconomic function and environmental protection function. Efforts to legalize the utilization of forests should be carried out under various schemes such as: community forest, village forest, or partnership. the agroforestry system can be selected as its land management system.